ANALISIS POLA SPASIAL DISTRIBUSI LONGSOR UNTUK PENENTUAN FAKTOR PENGONTROL UTAMA LONGSORLAHAN DI DAS KODIL JAWA TENGAH - , RINI MEIARTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Kodil Catchment Area has complete geomorphology condition in consequence of all sorts of litho logy and control of fault system. Geomorphology process especially landslide activity happen intensively. Due to intensively landslide activity, number and kind of landslides have variation. This study aims to determine main controlling factor as seen from the relationship between landslide spatial pattern and landslide parameters. Landslide parameters consist of landform, land use, slope, river networks, and road networks. Census data retrieval is done and then does the analysis of spatial patterns of distribution of landslides based nearest neighborhood. Determination of the main controlling factor is determined based on the percentage of landslides as a form of descriptive analysis. The results showed that the spatial pattern of slump to cluster and slide to dispersed. The main controlling factor of landslides in Kodil Catchment is human induced. Human induced such as the construction of roads and settlements that are not in accordance with the slope and soil characteristics. Moreover, shifting cultivation in fault-controlled landforms unit will form an intensive landslide